Many lenses for planetary health: seeding citizen engagement for sustainable futures visioning with new ways of seeing - Poland, Blake (Can J Public Health, 2020)
OBJECTIVES: This pilot project sought to seed citizen engagement processes for sustainable futures visioning with ideas, perspectives, and processes informed by Indigenous ways of knowing. METHODS: Five circle dialogues were convened with students, faculty, and members of the public, in the spring of 2019, using Indigenous talking circle methodology and intentionally seeded with “disruptive” ideas to encourage reflexivity and open space for “out-of-the-box” thinking. These were complemented by a series of one-on-one dialogues with members of the pan-Canadian research team. Pre- and post-dialogue surveys, notes taken by participants, team members, and co-facilitators, as well as notes from one-on-one interviews, constituted the data drawn upon for this paper. RESULTS: Participants were overwhelmingly positive about their experience, noting they were able to go further and deeper in their thinking and listening, and that they valued the Indigenous talking circle methodology, even if they stopped short of claiming the experience had transformed their way of seeing the world. Key points raised in the dialogues included the need for a more relational worldview, the need to repair severed relations with the land and nature, the importance of Indigenous ways of knowing, the importance of community building, and the need to question the fundamental assumptions undergirding contemporary Western societies. CONCLUSIONS: While caution must be exercised in drawing conclusions and extrapolating from this modest pilot project, our experience underscores the value of processes that intentionally catalyze critical reflexivity and openness to other ways of seeing, informed by Indigenous ways of knowing and talking circle methodology.